Strategy and Leadership in the "Emerging Era" (Post-Pandemic Digital World) - Palasamudram, Swathi (Digital Repository of Theses, 2024)
This research examines the interplay between strategy and leadership in the post-pandemic digital world, which is characterized by unprecedented change and complexity. This study aims to understand how leaders can formulate effective strategies to navigate this emerging era and identify the key competencies required for leaders to succeed in this environment. The study employs a mixed-methods approach, including a literature review, case studies, and a survey of executives from a range of industries. The findings reveal that the most successful leaders in the emerging era are those who are able to balance agility and stability, and who can effectively leverage digital technologies to drive innovation and efficiency. Leaders who prioritize collaboration, empathy, and inclusivity can better build cohesive and resilient teams and navigate the challenges of a rapidly changing environment. The study also identifies several competencies that are essential for leaders in the emerging era, including digital literacy, strategic thinking, emotional intelligence, and resilience. Leaders who possess these competencies are better able to navigate the complexity of the post-pandemic digital world, and to drive sustainable growth and innovation. Overall, this research highlights the critical role of leadership in shaping the future of organizations in the emerging era. By prioritizing the development of key competencies and embracing a strategic mindset that balances agility and stability, leaders can position their organizations for success in the post-pandemic digital world.